FOREIGN EXPERIENCE IN PERSONNEL MANAGEMENT IN THE HOTEL AND RESTAURANT BUSINESS (INNOVATIVE ECONOMY, 2020)
Okhota V.I. FOREIGN EXPERIENCE IN PERSONNEL MANAGEMENT IN THE HOTEL AND RESTAURANT BUSINESSPurpose. The aim of the article is systematization of the main directions of effective foreign experience of personnel management in the field of hotel and restaurant business.Methodology of research. The works of domestic and foreign scientists on effective foreign experience in personnel management in the hotel and restaurant business are the theoretical and methodological basis of the study. The tasks set in the work are solved by means of methods: analysis and generalization – at disclosure of the basic directions of the leading foreign experience of personnel management in the field of hotel and restaurant business; system approach and abstract and logical – in determining the possibilities of application of the considered methods in the domestic conditions of development of the subjects of the researched sphere.Findings. The main directions of effective foreign experience of personnel management in the field of hotel and restaurant business are systematized. It is established that the main areas of successful experience of foreign countries in the management of personnel of the hotel and restaurant industry include: the personnel management system of the hotel and restaurant industry, based on the use of kaizen strategy, which is typical of Japanese management; the American approach to the personnel management system, which is applied to the entire service sector in the country (including the hotel and restaurant business) and is based on a decent assessment and remuneration of employees for the work performed (“Pay for Performance”); competency approach used in the hotel and restaurant industry in the West and based on the guideline for training employees to manage their own knowledge, skills and abilities, i.e. be able to learn and develop independently (through the introduction of a generic model and corporate competency model).Originality. The substantiation of possible directions of adaptation of effective foreign experience of personnel management in the sphere of hotel and restaurant business to conditions of functioning of the Ukrainian establishments of the specified sphere has received further development.Practical value. The use of successful experience of foreign countries in the management of personnel of the hotel and restaurant industry will contribute to the further improvement of the system of training, retraining, advanced training and competitiveness of the hotel industry of Ukraine.Key words: personnel management, hotel and restaurant business, competency approach, kaizen strategy, implementation, generic model, corporate competency model, adaptation.
Keywords: Key words; personnel management; hotel and restaurant business; competency approach; kaizen strategy; implementation; generic model; corporate competency model; adaptation.